Resiliensi Iman Kristen dalam Refleksi Kehidupan Habakuk - Andreas Fernando; Carolina Etnasari Anjaya; Yonatan Alex Arifianto (Badan Musyawarah Perguruan Tinggi Keagamaan Kristen Indonesia, 2022)
The ministry and life of the prophet Habakkuk occurred in difficult times, but these conditions shaped the solidity of his faith in God. The prophet Habakkuk's response to the current situation can be a reflection and an example for God's people who live in today's era. This study aims to describe Habakkuk's experience of faith and provide his reflection on God's people so that they can have faith resilience when facing difficult situations and injustices in life. Qualitative methods are used in this study with a literature study approach and narrative excavation in the book of Habakkuk. The study yielded an understanding that all the problems, crushes, and burdens of life's questions actually led the prophet Habakkuk to seek and find God so that he obtained answers to questions, strength, guidance, and strength of faith from Him. This pattern can be applied in the lives of believers when faced with difficult situations and injustice through five steps of strengthening faith. First, open communication with God through the expression of the heart. Second, diligently waiting for God's answer by transforming the perspective from a human perspective to God's perspective. Third, to be His witness so that through the life experiences they go through, they can bring themselves and others to know God better. Fourth, patiently waiting for God's time for His help and acts of justice through prayer and thanksgiving. Fifth. Faith resilience will be formed when believers depend on God - rely on Him completely and make Him a source of strength. AbstrakPelayanan dan kehidupan nabi Habakuk terjadi dalam masa yang sulit, namun justru kondisi itu membentuk kekokohan imannya di dalam Tuhan. Respons nabi Habakuk atas keadaan yang terjadi dapat menjadi refleksi dan teladan bagi umat Tuhan yang hidup di zaman ini. Kajian ini bertujuan mendeskripsikan pengalaman iman Habakuk dan memberikan refleksinya bagi umat Tuhan agar dapat memiliki resiliensi iman ketika menghadapi situasi sulit dan ketidakadilan dalam hidup ini. Metode kualitatif dipergunakan dalam kajian ini dengan pendekatan studi pustaka dan penggalian narasi pada kitab Habakuk. Hasil penelitian menunjukkan bahwa segala persoalan, himpitan dan beban pertanyaan kehidupan justru membawa nabi Habakuk mencari dan menemukan Tuhan sehingga diperolehnya jawaban pertanyaan, kekuatan, tuntunan dan kekuatan iman dariNya. Pola ini dapat diterapkan dalam kehidupan orang percaya ketika menghadapi situasi sulit dan ketidakadilan melalui lima langkah penguatan iman. Pertama, membuka komunikasi dengan Tuhan melalui ungkapan hati. Kedua, transformasi cara pandang dari perspektif manusia kepada perspektif Tuhan. Ketiga, menjadi saksiNya agar melalui pengalaman kehidupan yang dilalui dapat membawa diri dan orang lain lebih mengenal Tuhan. Keempat, bersabar menantikan waktu Tuhan atas pertolongan dan tindakan keadilanNya melalui doa dan ucapan syukur. Kelima, resiliensi iman akan terbentuk tatkala umat percaya bergantung kepada Tuhan-mengandalkanNya secara penuh dan menjadikanNya sumber kekuatan.